2019
DOI: 10.1038/s41587-019-0268-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic kit for rice blight resistance

Abstract: Blight-resistant rice lines are the most effective solution for bacterial blight, caused by Xanthomonas oryzae pv. oryzae (Xoo). Key resistance mechanisms involve SWEET genes as susceptibility factors. Bacterial transcription activator-like (TAL) effectors bind to effector-binding elements (EBEs) in SWEET gene promoters and induce SWEET genes. EBE variants that cannot be recognized by TAL effectors abrogate induction, causing resistance. Here we describe a diagnostic kit to enable analysis of bacterial blight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 47 publications
4
115
0
Order By: Relevance
“…Considering that this particular pathogen strain has a functional type III secretion system that in other Xanthomonas pathogens is able to secrete TALEs into the plant cell and influence SWEET genes expression [59], a logical hypothesis was that Xaj417 would adopt this strategy. If this was the case, a disease control strategy could encompass the inactivation of a particular responsive SWEET member in walnut to deprive the pathogen from this sugar source, as recently shown for the rice blight pathosystem [60,61]. Since we observed no induction of specific SWEET genes in response to Xaj417 infection, we investigated the pathogen's genome in search of any known TALEs.…”
Section: Discussionmentioning
confidence: 94%
“…Considering that this particular pathogen strain has a functional type III secretion system that in other Xanthomonas pathogens is able to secrete TALEs into the plant cell and influence SWEET genes expression [59], a logical hypothesis was that Xaj417 would adopt this strategy. If this was the case, a disease control strategy could encompass the inactivation of a particular responsive SWEET member in walnut to deprive the pathogen from this sugar source, as recently shown for the rice blight pathosystem [60,61]. Since we observed no induction of specific SWEET genes in response to Xaj417 infection, we investigated the pathogen's genome in search of any known TALEs.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, researchers found that a mutation in the TalC EBE alone in the Kitaake background still could not confer resistance to African strains; instead a quintuple-mutant promoter lines (rice with mutated PthXo1, PthXo2, TalC, AvrXa7 and Tal5 EBEs) in the Kitaake background were moderately resistant to African strain AXO1947 [13]. Moreover, the sweet14 single-knockout mutant in the Kitaake background was also susceptible to African strain AXO1947, with a median lesion length of approximately 10 cm, whereas the sweet13;sweet14 double-knockout mutant showed complete resistance to African strains [18]. All of these previous studies demonstrated that single knockout of OsSWEET14 in the Kitaake background was unable to confer resistance to African strains.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread and long-term employment of BSR cultivars will likely increase the selection pressure on pathogen populations and increase the appearance of resistance-breaking strains (McDonald and Linde 2002;Mundt 2014). In the companion paper, a diagnostic kit named SWEET R kit 1.0 was developed to track the mutations of Xoo strains as well as to help farmers choose appropriate rice varieties that lack the binding sequences of the cognate TALes in the local Xoo populations (Eom et al 2019). To facilitate further research on BB pathosystems, this kit includes a SWEET promoter database, named SWEETpDB, to document EBEs across several rice accessions including Kitaake, Nipponbare, and Komboka.…”
mentioning
confidence: 99%
“…A Geographic Information System based decision tool named PathoTracer is included as well, which consolidates Xoo disease population and distribution research data within a user-friendly interface. In combination, these tools allow extension specialists and farmers to make educated decisions about appropriate resistant cultivar selection for the target rice growing regions experiencing BB pressure (Eom et al 2019).…”
mentioning
confidence: 99%